Genetic diversity and structure of wild and cultivated Amorphophallus paeoniifolius populations in southwestern China as revealed by RAD-seq - Yong Gao (Nature Portfolio, 2017)
Abstract Amorphophallus paeoniifolius, is a commercially important vegetable crop because of its high production potential. In this study, we generated a total of 166 Gb of genomic data from 16 wild and 20 cultivated A. paeoniifolius individuals in southwestern China using restriction site associated DNA sequencing (RAD-seq). We compared the genome-wide variations between the wild and cultivated populations. Wild populations exhibited higher genetic diversity than did cultivated populations based on private allele number, expected heterozygosity, observed heterozygosity and nucleotide diversity. STRUCTURE analysis, principal component analysis (PCA) and a maximum likelihood (ML) tree indicated that A. paeoniifolius populations could be divided into three groups (a cultivated group and two wild groups) with significant genetic differentiation. The low genetic diversity and shallow genetic differentiation found within cultivated populations are likely caused by continuous selection and the clonal propagation methods used during domestication. The significant differentiation between the wild populations may suggest strong genetic drift due to small populations and human disturbance. The genome-wide single nucleotide polymorphisms (SNPs) identified in our study will provide a valuable resource for further breeding improvement and effective use of the germplasm.